Analisis Pengaruh Good Public Governance Dan Nilai Organisasi Terhadap Kinerja Organisasi Sektor Publik - Oktavianto Nugraha Pratama; Titik Aryati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study discusses the impact of Good Public Governance and Organizational Values ​​on the Performance of Public Sector Organizations. This study aims to test and analyze the relationship between Good Public Governance and Organizational Values ​​on the Performance of Public Sector Organizations at the Directorate General of Customs and Excise. This study is included in quantitative descriptive research using cross-section data obtained through questionnaires. The sample used in this study was 105 employees of the Directorate General of Customs and Excise from various position groups, ages and years of service. Testing the data in this study uses the multiple linear regression analysis method by implementing classical assumption tests and hypothesis testing. The results of this study show that the Good Public Governance variable has a positive effect on the Performance of Public Sector Organizations and the Organizational Values ​​variable has a positive effect on the Performance of Public Sector Organizations. Keywords: Agency Theory, Good Public Governance, Organizational Values, Performance of Public Sector Organization